Are genetic tests informative in predicting food allergy?. Issue 3 (June 2016) - Li, Jin; Maggadottir, S. Melkorka; Hakonarson, Hakon
Abstract : Purpose of review: Food allergy is common among children and adults worldwide. Recent studies have improved our understanding of the genetic mechanism of food allergy and further studies may result in clinical application through genetic testing. Recent findings: Genetic factors are important in the development of food allergy. An increasing number of genes have been associated with food allergy in recent years. These include mutations and genetic variants in the filaggrin gene, the association of human leukocyte antigen DR and DQ regions with food allergy, copy number variation impacting CTNNA3 and RBFOX1, DNA methylation that partially mediates single nucleotide polymorphism association at the HLA-DR and DQ loci, as well as other genes. Several studies have implicated differences in gut microbiota composition in food allergy. Summary: With the advance of high-throughput genotyping and sequencing techniques together with improved analytical methods, the contributions of genetic and environmental factors in development of food allergy are being clarified. Yet much remains to be explored and more studies with larger sample sizes, better phenotyping, and improved quality control genomics methods are needed. The ultimate goal is the development of a panel of reliable markers for genetic testing in food allergy to improve overall patient care.